Bioleaching of E-Waste: Influence of Printed Circuit Boards on the Activity of Acidophilic Iron-Oxidizing Bacteria - Anaya-Garzon, Juan; Hubau, Agathe; Joulian, Catherine; Guezennec, Anne-Gwénaëlle (Frontiers in Microbiology, 2021)
Bioleaching is a promising strategy to recover valuable metals from spent printed circuit boards (PCBs). The performance of the process is catalyzed by microorganisms, which the toxic effect of PCBs can inhibit. This study aimed to investigate the capacity of an acidophilic iron-oxidizing culture, mainly composed of Leptospirillum ferriphilum, to oxidize iron in PCB-enriched environments. The culture pre-adapted to 1% (w/v) PCBs content successfully thrived in leachates with the equivalent of 6% of PCBs, containing 8.5 g L-1 Cu, 8 g L-1 Fe, 1 g L-1 Zn, 92 mg L-1 Ni, 12.6 mg L-1 Pb, and 4.4 mg L-1 Co, among other metals. However, the inhibiting effect of PCBs limited the microbial activity by delaying the onset of the exponential iron oxidation. Successive subcultures boosted the activity of the culture by reducing this delay by up to 2.6 times under batch conditions. Subcultures also favored the rapid establishment of high microbial activity in continuous mode.